Synthesis and Reactivities of Conducting Hexathienylbenzene-Co-Poly(3-Hexylthiophene) Star-Branched Copolymer as Donor Material for Organic Photovoltaic Cell - Ramoroka, Morongwa E.; Mdluli, Siyabonga B.; John-Denk, Vivian S.; Januarie, Kaylin C.; Modibane, Kwena D.; Nwambaekwe, Kelechi C.; Yussuf, Sodiq T.; Mokwebo, Kefilwe V.; Williams, Avril R.; Iwuoha, Emmanuel I. (Frontiers in Materials, 2022)
The hexathienylbenzene-co-poly(3-hexylthiophene-2,5diyl) (HTB-co-P3HT) conducting polymer was synthesized by oxidative co-polymerization of hexathienylbenzene (HTB) and 3-hexylthiophene using iron chloride (FeCl3) as an oxidant. The effect of chlorobenzene, toluene and chloroform on the optoelectronic characteristics of the polymer was investigated. The study revealed that spectroscopic and electrochemical responses of HTB-co-P3HT are affected by the nature of the solvent. The LUMO and HOMO energy levels of HTB-co-P3HT were determined from cyclic voltammetry and were compared to those of PC71BM and it was found that the LUMO energy levels of HTB-co-P3HT in toluene were lower than those for chlorobenzene and chloroform. The EIS analysis also revealed the thin film of HTB-co-P3HT prepared using toluene as the most conductive. However, the photovoltaic parameters of the HTB-co-P3HT OPV device departed from the favored toluene and noted chlorobenzene as being the advantageous solvent. We obtained a power conversion efficiency (PCE) of 0.48%, fill factor (FF) of 27.84%, current density (JSC) of 4.93 mA.cm-2 and open circuit voltage (VOC) of 0.35 V in chlorobenzene, a PCE of 0.30%, FF of 26.08%, JSC of 5.00 mA.cm-2 and VOC of 0.23 V in chloroform and finally, a PCE of 0.33%, FF of 25.45%, JSC of 5.70 mA.cm-2 and VOC of 0.23 V in toluene.